2007
DOI: 10.1210/en.2006-1394
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Induced Activation of Hypoxia-Inducible Factor-1α, Vascular Endothelial Growth Factor Expression, and Edema in the Uterus Are Mediated by the Phosphatidylinositol 3-Kinase/Akt Pathway

Abstract: Vascular endothelial growth factor (VEGF) plays an essential role in normal uterine physiology and function as well as endometrial cancer and other uterine disorders. Recently we showed that estrogen regulation of VEGF expression in the rat uterus involves rapid recruitment of both estrogen receptor (ER)-alpha and hypoxia-inducible factor (HIF)-1alpha to the VEGF promoter. Estrogen is known to stimulate both the MAPK and phosphatidylinositol 3-kinase (PI3K) pathways, which have been linked to the activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 86 publications
7
102
1
Order By: Relevance
“…The VEGF stimulates angiogenesis by promoting endothelial cell proliferation, and its expression is regulated by the HDAC activity (27). A previous study reported that the levels of VEGF were elevated significantly in endometrial cancer (28). In the present study, apicidin reduced the levels of VEGF significantly in the apicidin-treated group compared to the vehicle group, which showed increased levels of VEGF.…”
Section: Discussionsupporting
confidence: 58%
“…The VEGF stimulates angiogenesis by promoting endothelial cell proliferation, and its expression is regulated by the HDAC activity (27). A previous study reported that the levels of VEGF were elevated significantly in endometrial cancer (28). In the present study, apicidin reduced the levels of VEGF significantly in the apicidin-treated group compared to the vehicle group, which showed increased levels of VEGF.…”
Section: Discussionsupporting
confidence: 58%
“…It is interesting to note that the spatial expressions of estrogen and VEGF during pregnancy show the same pattern, i.e., their levels are both low in early pregnancy and high in late pregnancy (1). Further, VEGF promoter regions contain responsive elements for both estrogen and HIF-1α (18,22,29). However, we do not know whether HIF-1α increases with pregnancy, and our initial VEGF studies (unpublished) could not successfully detect HIF-1α using immunohistochemistry.…”
Section: Fig 1 Optimization Of Vegf Treatment In Mice Uterine Cervixmentioning
confidence: 86%
“…VEGF has been considered to be a target gene for the estrogen receptors and to contribute to breast cancer progression (Applanat et al, 2008;Khosravi Shahi et al, 2009). Estroegens are known to enhance VEGF expression (Kazi and Koos, 2007) and in breast tumors in vivo, estrogens has been shown to promote angiogenesis and increase extracellular VEGF . Garvin et al (2006) also demonstrated that similar events also occurred in ex vivo cultured normal human breast tissue (Garvin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%